2017
DOI: 10.29121/granthaalayah.v5.i10.2017.2312
|View full text |Cite
|
Sign up to set email alerts
|

Socio - Economic Determinants of Households Fuel Consumption in Nigeria

Abstract: Attainment of universal access to affordable, reliable, sustainable and modern energy is one of the goals for Sustainable Development Goals (SDGs). Existing data and statistic suggest that high proportion of households in less developed countries heavily rely on solid fuels for domestic requirements. Also, recent data revealed that in Nigeria over 70 percent of households depend on fuel wood for cooking which indicate the task ahead of policy makers in the country for ensuring access to efficient sources of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
(10 reference statements)
4
11
0
Order By: Relevance
“…Despite the difference in consumption of biomass fuel in different areas in the country, the biomass fuel coverage in the study area is high and responsible for increased amount of household air pollution. The implication of high biomass usage might be related with its easy accessibility and lower cost when compared with the cleaner fuel [ 21 ]. The result of this study indicated that the two weeks' prevalence of ARI among children under five years was 16.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the difference in consumption of biomass fuel in different areas in the country, the biomass fuel coverage in the study area is high and responsible for increased amount of household air pollution. The implication of high biomass usage might be related with its easy accessibility and lower cost when compared with the cleaner fuel [ 21 ]. The result of this study indicated that the two weeks' prevalence of ARI among children under five years was 16.2%.…”
Section: Discussionmentioning
confidence: 99%
“…The second methodological approach focuses mostly on the investigation of energy ladder hypothesis validity using discrete choice frameworks (Buba et al, 2017;Farsi and Filippini, 2007;Heltberg, 2005). However, these studies reveal mixed evidence regarding income and choice of fuel type especially in the sub Saharan Africa and other developing country context.…”
Section: Survey Approaches and Methods On Cooking Fuel Choicementioning
confidence: 99%
“…To date, the Sub Saharan Africa region and other developing countries face limited access to affordable and clean energy sources. It is estimated that 2.5 billion people depend on solid fuel from traditional biomass fuels such as crop residues and firewood for cooking and heating which are associated with indirect adverse health effects (Buba et al, 2017). This number is projected to reach 2.7 billion by 2030 implying that depletion of forest and environmental degradation might be inevitable if proper and timely policy measures are sluggish (IEA, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Another study carried out by Buba et al (2017) [8] noted that attainment of universal access to affordable, reliable, sustainable and present day power is one of the dreams for Sustainable Development Goals (SDGs). Existing information and statistic advocate that excessive share of households in much less developed international locations closely be counted on strong fuels for home requirements.…”
Section: Literature Reviewmentioning
confidence: 99%